Pus in Spinal Needle: Diagnosis and Management of a Long-Segment Spinal Epidural Abscess. (28th April 2021) - Munasinghe, B. M.; Pathirage, N.; Hameed, M. S.; Hapuarachchi, C. T.
Abstract : Spinal-epidural abscess (SEA) is believed to be primarily of haematogenous origin and very rarely as a consequence of central neuraxial blockade. Early diagnosis and pertinent management invariably improve neurological outcomes. We report a case of long-segment SEA, which was suspected during subarachnoid anaesthesia, subsequently diagnosed and managed appropriately, averting irreversible neurological deficits.